Conception Prodigious Supervision Contact with Medical Students Provides Professional Experience - Saleh, Nor Shela; Mohd Shafie Rosli; Lutfan Jaes; Khairunesa Isa; Siti Sarawati Johar; Muhaymin Hakim Abdullah; Ku Hasnan Ku Halim; Md Akbal Abdullah (Human Sustainability Procedia, 2023)
Experience matters when it comes to learning outcomes. Experience can be gained by applying knowledge and skills and working with supervisors. This study investigates the supervisor’s role in assisting doctor trainees in making the connection between the use of knowledge and skills and the achievement of learning experiences. The learning is geared towards housemanship. This research focuses on three main goals. Examine first the level of knowledge and skills of trainee doctors, then the level of experience of trainee doctors, and finally the role of supervision as a moderator in the relationship between knowledge and skills and trainee doctors’ experience. The research employs a quantitative approach. Descriptive and inferential methods were used to analyse the study. The first and second objectives were accomplished through descriptive analysis. For the third objective, inferential analysis (hierarchical regression) was used. There were 303 total respondents identified, with 172 female trainee doctors and 65 male trainee doctors. Malays make up most respondents, followed by Chinese, Indians, and others. The first objective demonstrates that most trainee doctors possess advanced knowledge and skills. The second objective, level of experience, reveals that 61.72 percent of trainee doctors have extensive experience. The findings of the third objective study show that supervision is important in assisting doctor trainees in gaining experience through the influence of knowledge and skills. It is evidence that the supervisor’s role is to guide, facilitate, and instruct the trainee doctor as they progress through housemanship.